Biological and ecological diversity of aquatic macroinvertebrates in response to hydrological and physicochemical parameters in tropical forest streams of Gunung Tebu, Malaysia: implications for ecohydrological assessment. Issue 2 (24th February 2013) - Md Rawi, Che Salmah; Al‐Shami, Salman Abdo; Madrus, Madziatul Rosemahanie; Ahmad, Abu Hassan
ABSTRACT In this study, we have investigated the effects of some hydrological and physicochemical parameters such as water quality, velocity, water depth, river width, water pH, water temperature, ammonia‐N, biochemical oxygen demand (BOD), chemical oxygen demand (COD) and dissolved oxygen (DO) on diversity of aquatic macroinvertebrates in forest streams of Gunung Tebu (GT), Malaysia. The results of canonical correspondence analysis identified three groups of the aquatic macroinvertebrates according to their relationships with hydrological and physicochemical parameters. The stream velocity, water quality (i.e. DO, BOD and ammonia‐N) in addition to canopy cover, total habitat score and substrate quality were the determinant factors controlling the diversity pattern of the aquatic macroinvertebrates in GT streams. Alteration in the hydrological and physicochemical parameters showed to influence the ecological diversity of the aquatic macroinvertebrates in GT streams. The predators were found to be highly associated with the elevated concentrations of BOD and COD. Shredders were positively correlated with pH, stream velocity, DO and habitat quality indicators (total habitat score, embeddedness, epifaunal and canopy cover). However, the collector‐gatherers correlated negatively with all of these parameters. It was concluded that stream velocity, substrate structure and water quality were strong attributes for variation in aquatic macroinvertebrate assemblage structure in tropical forest streams of GT. Copyright © 2013 John Wiley & Sons, Ltd.